Follicular adenoma associated with spindle cell proliferation, papillary adenoma and colloid goitre in a dromedary camel. (January 2016) - Tageldin, Mohamed; Damir, Hassan; Omer, Elhag; Ali, Mahmoud; Adam, Adam
Abstract In humans, spindle cell lesions associated with thyroid adenoma or carcinoma are rare. A cross section of the thyroid of a dromedary camel showed follicular cysts, and microscopically, both thyroid lobes showed colloid goitre. The left lobe showed spindle cell proliferation associated with follicular adenoma without evidence of capsular or vascular invasion. The spindle cell lesion had cells featuring ground glass or pseudoinclusion nuclei and showed extensive haemorrhage, hyalinization and thrombosis. The right thyroid lobe showed papillary adenoma. Immunohistochemistry showed negative expression for malignancy. Serum Se, free tri-iodothyronine (fT3) and free thyroxine (fT4) values were low and CK activity was high. The histological features were unusual and merit reporting.